The Effectiveness of Student Centre Learning in Experiment Method on Acid and Base Solution to Increase Student Achievement - Marpaung, Dewi Natalia; Azzajjad, Muhammad Fath (Journal of Applied Science, Engineering, Technology, and Education, 2020)
The purpose of this research was to know the effectiveness of student centre learning (SCL) based experiment method to increase student achievement on topic acid-based solution, type of this research descriptive qualitative, this research was conducted in SMAN 16 Medan the sample that used in this experiment consist of two class which is grade XI IPA1 as experiment class that treated by using student centre learning and Grade of XI IPA 2 as a control class with about student centre learning-based experiment method. Data in this research got from pretest which is given before treated the method and posttest after treated the method. In experimental class, the mean before teaching treatment is = 34, while after giving treatment the mean is increase become 70. In controlled class, the mean before teaching treatment is = 29, while after teaching treatment it changes become 42. The study concludes that the SCL based experiment method is an effective method in the teaching of the acid-based solution to increase student achievement.